Simulation study of micro wind turbine
The micro wind turbine is an innovative technology that can generate electricity with a low wind speed condition. This electricity is produced from a kinetic energy which is harvested by the wind turbine and the particular energy is converted into electrical energy. Currently, the technology of conventional wind turbine cannot be used at an urban area or rural area because that type of turbine is large in sizing and only will be generating electrical power at the minimum wind speed of around 4 m/s and in order to be efficient, its require wind speed over 7 m/s. Therefore, by using the micro wind turbine, it allows energy to be harvested at wind speed as low as 2 m/s and the energy have generated effectively. In this project, MATLAB software is used to design the arrangement of micro wind turbine system by using wind turbine DC generator. The configuration arrangement of micro wind turbine generator is in parallel, series and series-parallel for wind turbine DC generator in order to investigate the effectiveness of each arrangement. The boost converter is used to step-up the electrical energy that generated by the micro wind turbine. The output voltage, current and power are analysed by varying the wind speed in a range 1.9 m/s to 2.5 m/s maximum. In summary, the series wind turbine DC generators configuration arrangement can be applied to lighting system where it require an adequate level of voltage to function properly. Meanwhile, the suitable application for parallel configuration for DC generators micro wind turbine is a charging system such as power bank where higher level of output current is required. Furthermore, highest output power can be produce, when the micro wind turbines DC generator is connected in series-parallel configuration. This can be seen from the simulation result, these configurations had higher output voltage, current and power which were 30.58 V, 1.596 A and 21.86 W respectively. Therefore, DC power generation with the micro wind turbine is suitable for low wind speed since the system can produce adequate electrical power with wind speed as low as 1.9 m/s.